Kosztolányi Dezső és Ovidius Fasti című műve - Takács, László (Studia Litteraria, 2018)
Dezső Kosztolányi published three sonnets (Christmas, Easter, Pentecost) in 1905 with the common title Fasti. This title might serve as an allusion to the work of the roman poet, ovid, who composed a poem on the roman calendar. Kosztolányi’s letters and other writings confirm that he was reading ovid’s poems that year, and it is obvious that he knew ovid’s Metamorphoses and Fasti as well. It is Kosztolányi’s innovation to connect the most important Christian holidays using the ancient pagan terminus. What is more, the representation of the three feasts does not only resemble the viewpoint of Parnassian poetry, but also ovid’s mode of representation. The Christian elements reappear in a profane context.